An essential role of disulfide bonds for the hierarchical self-assembly and underwater affinity of CP20-derived peptides - Li, Baoshan; Song, Junyi; Mao, Ting; Zeng, Ling; Ye, Zonghuang; Hu, Biru (Frontiers in Bioengineering and Biotechnology, 2022)
Barnacles are typical fouling organisms strongly adhere to immersed solid substrates by secreting proteinaceous adhesives called cement proteins (CPs). The self-assembly of the CPs forms a permanently bonded layer that binds barnacles to foreign surfaces. However, it is difficult to determine their natural structure and describe their self-assembly properties due to the abundance of cysteines in whole-length CP20. A putative functional motif of Balanus albicostatus CP20 (BalCP20) was identified to present distinctive self-assembly and wet-binding characteristics. Atomic-force microscopy (AFM) and transmission electron microscope (TEM) investigations showed that wildtype BalCP20-P3 formed grain-like spindles, which assembled into fractal-like structures like ears of wheat. SDS-PAGE, AFM, and LSCM showed that DTT treatment opened up disulfide bonds between cysteines and disrupted fractal-like structures. Additionally, these morphologies were abolished when one of the BalCP20-P3 four cysteines was mutated by alanine. Circular dichroism (CD) results suggested that the morphological diversity among BalCP20-P3 and its mutations was related to the proportion of α-helices. Finally, quartz crystal microbalance with dissipation (QCM-D) detected that BalCP20-P3 and its mutations with diverse self-assemblies occupied different affinities. The above results demonstrated that cysteines and disulfide bonds played a crucial role in the self-assembly and wet binding of BalCP20-P3. The work provides new ideas for the underwater bonding of BalCP20 and developing new bionic underwater adhesives.